Mengonstruksi Instrumen Penilaian Afektif dalam Pembelajaran Pendidikan Agama Islam - Nadhuha; Haryanti, Tutik; Risnawati (GHIROH, 2024)
Assessment or what is now more commonly referred to as assessment is a series of activities that must be carried out by a teacher in the learning process. So that this learning assessment is used by the teacher to measure the achievement of learning objectives in the classroom. Assessment is an integrated part of the learning process because it provides holistic information and provides feedback for teachers, students and parents/guardians of students to guide them in determining the next learning strategy. Assessment is divided into three major domains, namely the cognitive, affective and psychomotor domains. In this paper the author focuses on attitude assessment which aims to provide an overview of the development of an attitude scale assessment instrument that can be used to measure students' affective abilities as seen from the Likert, Thurstone and Guttman scale attitude assessments in PAI subjects. The method used is literature review or library research. From the results of data analysis, it was found that the attitude assessment of the Likert, Thurstone and Guttman scales was very appropriate for use in PAI subjects.